Genotoxicidad de tres concentraciones de acetaminofeno paracetamol® en células de médula ósea de mesocricetus auratus - Amésquita Cárdenas, María Leticia (2009)
The purpose of this work was determining the gene-toxic damage of three concentrations of the acetaminophen paracetamol® in Mesocricetus auratus bone marrow cells, and in order to achieve this, five groups were established. These groups were treated with physiological saline solution (negative control), 50 mg/kg/pc. of cyclophosphamide (positive control) and 125, 500, 1000 mg/kg/pc. paracetamol® daily for 10 days. After the last administration, the bone marrow was isolated and processed with a micronucleus test, obtaining chromosomes and organizing the nucleolus regions (AgNOR). A significant increase of micronuclei (MN) was observed in different concentrations of paracetamol® (25.33 ± 4.04*, 31.0 ± 1.0*y 36.33 ± 0.58*) and cyclophosphamide (45.66 ± 7.37*) respectively, regarding the negative control (7.16 ± 0.28 *). It was also noted that there was a variation in the number and size of the micronucleus in polychromatic erythrocytes. Regarding chromosomal alterations, a significant increase was observed in different concentrations of acetaminophen paracetamol® (25.33 ± 4.04*, 31.0 ± 1.0*and 36.33 ± 0.58*) and cyclophosphamide (45.66 ± 7.37*) relative to the negative control (1.66. ± 0.58). Also it was observed some three radials exchanges and complex rearrangements, broken chromatids with non centric fragment in different concentrations of acetaminophen and positive control but not in the negative control. In the evaluation of morphology of the Nucleolar Organizer Regions (AgNOR) in bone marrow cell of M. auratus some differences were found statistically significant among areas of AgNOR/cell 3.37 ± 0.56 *; 2.38 ± 0.82 *; 3.95 ±1.02* and 3.03 ± 0.63 * µm2 for acetaminophen and cyclophosphamide respectively, in relation to the cells of specimens of the negative control group (1.74 ± 0.35 *); general form that treated cells with paracetamol® induced AgNOR pleomórficos. In conclusion, acetaminophen paracetamol® increases the frequency of micronucleus test in polychromatic erythrocytes, broken chromatids in the chromosomes and a high significance in morphometric variations nucleolar organizer regions (AgNOR) in bone marrow cells M. auratus.